دور الإدارة الإلكترونية في ضمان فعالية المرفق العام في تحقيق المصلحة العامة - حمياز سمير; بخوش سامي (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
يحاول الموضوع محل الدراسة، البحث في دور الإدارة الإلكترونية كأحد الأساليب الحديثة للتنمية الإدارية في ضمان فعالية المرفق العام في تحقيق المصلحة العامة، من خلال إبراز وتبيان الآثار الإيجابية المترتبة عن التطبيق السليم والناجح للإدارة الإلكترونية ليس فقط على المبادئ الحاكمة لسير المرفق العام والراعية للمصلحة العامة، وإنما أيضا الزيادة من كفاءة وفعالية الأداء الإداري لهذه المرافق، فضلا عن تكريس قيم الحكم الراشد، كالشفافية، الحياد، التقليل من الفساد، ورضا المواطن..، الأمر الذي يؤدي إلى ضمان المصلحة العامة وتحسين جودة الخدمة العمومية. الكلمات المفتاحية: الإدارة الإلكترونية؛ المرفق العام؛ المصلحة العامة؛ الفعالية؛ الكفاءة الإدارية. Abstract: This study attempts to highlight the role of electronic management as one of the modern methods of administrative development in ensuring the effectiveness and performance of the public service in achieving the public interest, by highlighting the positive effects of the proper application of electronic management on the principles governing the operation of the public service and the principles of public interest. This research tries also to demonstrate the role of electronic management in achieving the administrative performance, and to promote the values of good governance, such as transparency, reducing corruption.., thus ensuring public interest Keywords: Public Service; Electronic Management; Public Interest; Efficiency; Administrative Performance.